Great humor Including wit, whimsy, and satire from the remote past to the present - 20160731 frey50; Untermeyer, Louis (McGraw-Hill Book Company New York, 1972)
A treasury of humor including wit, whimsy, and satire from the remote past to the present
The Bible -- Aesop -- The Panchatantra -- The Greek anthology -- Anacreon -- Horace -- Juvenal -- Ovid -- Martial -- Petronius -- Lucian -- Gesta Romanorum -- Giovanni Boccaccio -- Geoffrey Chaucer -- Francois Villon -- Erasmus -- The renaissance parable -- Francois Rabelais -- Miguel de Cervantes -- Thomas Dekker -- John Donne -- Ben Jonson -- Sir John Suckling -- Samuel Butler -- Jean de la Fontaine -- Moliere -- La Rochefoucauld -- John Dryden -- Jonathan Swift -- Joseph Addison -- John Gay -- Alexander Pope -- Voltaire -- Benjamin Franklin -- Henry Fielding -- Laurence Sterne -- Robert Burns -- Sydney Smith -- Charles Lamb -- Washington Irving -- George Gordon, Lord Byron -- William Makepeace Thackeray -- Charles Dickens -- Edward Lear -- Charles Stuart Calverley -- Charles Lutwidge Dodgson (Lewis Carroll) -- Samuel Langhorne Clemens (Mark Twain) -- Paul Bunyan -- W.S. Gilbert -- Ambrose Bierce -- Anatole France -- Oscar Wilde -- A.E. Housman -- Stephen Leacock -- H.H. Munro (Saki) -- Max Beerbohm -- Guy Wetmore Carryl -- William Somerset Maugham -- P.G. Wodehouse -- Damon Runyon -- Edith Sitwell -- Robert Benchley -- Dorothy Parker -- James Thurber -- Isaac Bashevis Singer -- S.J. Perelman -- Joseph Heller.
Includes index
Keywords: Wit and humor